Place Management at the City of Swan – A Whole‐of‐City Approach. Issue 4 (25th October 2016) - Bishop, Mark
Abstract : Local government often consists of a diverse array of local communities, but remains ideally placed to work with communities in responding to challenges at a local 'place' level, as well as broader regional issues. The City of Swan, Western Australian (WA) recognised that it required a more adaptable and place focussed approach to the planning and delivery of services to its large and diverse communities. This has led to the adoption of a place management approach at the City, including the division of the City into five smaller place management areas, based around communities of shared interest. This article highlights the application of place management as it has been applied across the City of Swan, including lessons learnt to date. Abstract : This article describes a set of policy initiatives of the ACT government aimed at building not‐for‐profit sector capacity. It argues the need for comparative studies of similar initiatives across Australian jurisdictions.